2021
DOI: 10.1038/s41467-021-22191-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete polarization of electronic spins in OLEDs

Abstract: At low temperatures and high magnetic fields, electron and hole spins in an organic light-emitting diode become polarized so that recombination preferentially forms molecular triplet excited-state species. For low device currents, magnetoelectroluminescence perfectly follows Boltzmann activation, implying a virtually complete polarization outcome. As the current increases, the magnetoelectroluminescence effect is reduced because spin polarization is suppressed by the reduction in carrier residence time within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Recently, magneto­electro­luminescence (MEL) has been used as an effective and sensitive detection tool to visualize the spin-related behavior of microscopic processes in various OLEDs. For example, Peng et al found high-level reverse intersystem crossing (HL-RISC) from high-lying triplet to S 1 states in N , N -diphenyl-4-(9-phenyl­naphtho-[2,3- c ]­[1,2,5]­thia­diazol-4-yl)­aniline-based OLEDs through MEL measurements . Scharff et al probed the complete polarization of electronic spins in OLEDs via analyzing temperature- and current-dependent MEL responses . Guo et al used MEL measurements to unravel the important role of the spin conversion process between high-lying triplet and S 1 states in aggregation-induced, emission-based OLEDs .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, magneto­electro­luminescence (MEL) has been used as an effective and sensitive detection tool to visualize the spin-related behavior of microscopic processes in various OLEDs. For example, Peng et al found high-level reverse intersystem crossing (HL-RISC) from high-lying triplet to S 1 states in N , N -diphenyl-4-(9-phenyl­naphtho-[2,3- c ]­[1,2,5]­thia­diazol-4-yl)­aniline-based OLEDs through MEL measurements . Scharff et al probed the complete polarization of electronic spins in OLEDs via analyzing temperature- and current-dependent MEL responses . Guo et al used MEL measurements to unravel the important role of the spin conversion process between high-lying triplet and S 1 states in aggregation-induced, emission-based OLEDs .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Because the rate of RISC in the TADF-based OLEDs depends on the activation energy ( E act ) of RISC, the MPL caused by the field-modulated RISC should also be activated. Figure d plots MPL versus temperature in the temperature range from 310 to 190 K. It is shown that MPL of both doped and undoped samples can be well fitted by the following Arrhenius equation: where k B is Boltzmann’s constant and T is the temperature, confirming that the field-modulated RISC channel is indeed activated. The linear fit at high temperatures gives an activation energy E act of ∼24 meV for the TADF material doped with a spin sensitizer and an E act of ∼48 meV for the TADF material without a spin sensitizer, which are of the order of k B T at room temperature (∼26 meV) and also in agreement with that (∼50 meV) obtained in a previous report .…”
mentioning
confidence: 75%
“…The underlying microscopic mechanisms for spin-pair states in Device 1 are schematically displayed in Figure e. Initially, electrons and holes are injected from opposite electrodes and recombine under the Coulombic attraction, then form weakly bound singlet and triplet polaron pairs (i.e., PP 1 and PP 3 ) in the emission layer. , PP 1 and PP 3 can undergo the interconversion (i.e., PP-ISC and PP-RISC processes) because they are almost degenerate in energy, and the spin flipping in the PP states can be realized under the hyperfine interaction (HFI) with the scale of several milli-Tesla. Next, PP 1 and PP 3 will dissociate back into free carriers or form EX 1 and EX 3 with rate constants of k S and k T . Note that the interconversion of PP states is frequently dominated by the PP-ISC process (PP-ISC, PP 1 → PP 3 ) because k T is generally larger than k S .…”
Section: Resultsmentioning
confidence: 99%